Translation Method of Emotional Expression in Daniel Keyes’ The Minds of Billy Milligan - Wanodya, Ayuning; Anggraeni, Diana; Sigalingging, Bob Morison (Universitas Sanata Dharma, 2024)
This study examines the English to Indonesian translation of emotional expressions depicted in Daniel Keyes’s novel “The Minds of Billy Milligan” and its Indonesian translation “24 Wajah Billy.” The primary objectives are to describe the emotional expressions portrayed by the main character and to analyze the methods applied in translating these emotional expressions from English to Indonesian. Employing David Krech’s emotional classification theory and drawing on Vinay and Darbelnet’s translation methods, this qualitative descriptive research identifies 28 emotional classification data in the novel. Eight types of emotion classifications were identified, including 13 instances of fear, 6 instances of anger, 3 instances of hate, 2 instances of happiness, 1 instance of pain, 1 instance of guilt and regret, 1 instance of pride and shame, and 1 instance of love. The translation applies six translation methods used in 39 instances borrowing, literal, transposition, modulation, equivalent, and adaptation. Each emotion is translated using different translation methods. The application of these six methods is divided into three variants: single with 18 instances, couplet with 9 instances, and triplet with 1 instance. The literal method is the most frequently used in translating emotional expression. The translation method aims to preserve the essence of the narrative from the source language to the target language.